Adalimumab Therapy is Effective and Well Tolerated in AS, RA, and PsA Patients with a History of Insufficient Response or Intolerance to Other Anti—TNF Therapies - Vinall, Phil (MD Conference Express, 2008)
This article discusses data from RHAPSODY [NCT00478660; AS], ReAct [NCT00650026; RA], and STEREO [NCT00235885; PsA] - 3 open-label trials that examined the effectiveness of adalimumab treatment in patients with ankylosing spondylitis, rheumatoid arthritis, or psoriatic arthritis who had a history of anti-TNF therapy.